Molecular and functional profiling of cell diversity and identity in the lateral superior olive, an auditory brainstem center with ascending and descending projections - Maraslioglu-Sperber, Ayse; Pizzi, Erika; Fisch, Jonas O.; Kattler, Kathrin; Ritter, Tamara; Friauf, Eckhard (Frontiers in Cellular Neuroscience, 2024)
The lateral superior olive (LSO), a conspicuous integration center in the auditory brainstem, contains a remarkably heterogeneous neuron population. Ascending neurons, predominantly principal neurons (pLSOs), process interaural level differences for sound localization. Descending neurons (lateral olivocochlear neurons, LOCs) provide feedback into the cochlea and likely protect from acoustic overexposure. The molecular determinants of the neuronal diversity in the LSO are largely unknown. Here, we employed patch-seq analysis in juvenile mice to classify LSO neurons by their functional and molecular profiles, including developmental aspects. Across the sample (n = 86), genes involved in ATP synthesis were particularly highly expressed, confirming the energy expenditure of auditory neurons. Two clusters were identified, pLSOs and LOCs. They were distinguishable by 353 differentially expressed genes (DEGs), most being novel for the LSO. Electrophysiological analysis corroborated the transcriptomic clustering. We focused on genes impacting neuronal input-output properties and validated some by immunohistochemistry, electrophysiology, and pharmacology. These genes encode proteins like osteopontin, Kv11.3, and Kvβ3 (pLSO-specific), calcitonin-gene-related peptide (LOC-specific), or Kv7.2 and Kv7.3 (no DEGs). We identified 12 ‘Super DEGs’ and 12 genes demonstrating ‘Cluster similarity’. Collectively, we provide fundamental and comprehensive insights into the molecular composition of individual ascending and descending neurons in the juvenile auditory brainstem and how this may relate to their specific functions, including developmental aspects.